Distinct role of nuclear receptor corepressor 1 regulated de novo fatty acids synthesis in liver regeneration and hepatocarcinogenesis in mice. Issue 3 (26th January 2018) - Ou‐Yang, Qing; Lin, Xi‐Meng; Zhu, Yan‐Jing; Zheng, Bo; Li, Liang; Yang, Ying‐Cheng; Hou, Guo‐Jun; Chen, Xin; Luo, Gui‐Juan; Huo, Feng; Leng, Qi‐Bin; Gonzalez, Frank J.; et al.
Abstract : It is urgent that the means to improve liver regeneration (LR) be found, while mitigating the concurrent risk of hepatocarcinogenesis (HCG). Nuclear receptor corepressor 1 (NCoR1) is a co‐repressor of nuclear receptors, which regulates the expression level of metabolic genes; however, little is known about its potential contribution for LR and HCG. Here, we found that liver‐specific NCoR1 knockout in mice ( NCoR1 Δhep ) dramatically enhances LR after partial hepatectomy and, surprisingly, blocks the process of diethylnitrosamine (DEN)‐induced HCG. Both RNA‐sequencing and metabolic assay results revealed improved expression of Fasn and Acc2 in NCoR1 Δhep mice, suggesting the critical role of de novo fatty acid synthesis (FAS) in LR. Continual enhanced de novo FAS in NCoR1 Δhep mice resulted in overwhelmed adenosine triphosphate ATP and nicotinamide adenine dinucleotide phosphate (NADPH) consumption and increased mitochondrial reactive oxygen species production, which subsequently attenuated HCG through inducing apoptosis of hepatocytes at an early stage after DEN administration. Conclusion: NCoR1 functions as a negative modulator for hepatic de novo FAS and mitochondria energy adaptation, playing distinct roles in regeneration or carcinogenesis. (Hepatology 2018;67:1071–1087)